2014
DOI: 10.5114/jcb.2014.43248
|View full text |Cite
|
Sign up to set email alerts
|

Pre-plan parameters predict post-implant D 90 ≥ 140 Gy for 125 I permanent prostate implants

Abstract: PurposeTo find permanent prostate implant (PPI) pre-plan dosimetric parameters that predict post-implant D90 ≥ 140 Gy.Material and methodsPre-plans were evaluated for 504 patients undergoing PPI with 125I seeds for low or intermediate risk prostate cancer. Baseline patient and disease factors, numbers of seeds, ratios of number of seeds to available positions (occupancy proportion), and distances between the 100% isodose line and edge of the prostate (margin) planned for the whole prostate (WP), superior (S), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Pre-planning technique, intraoperative approach, and dosimetric evaluation have previously been described in detail [ 13 , 14 ]. The brachytherapy target volume consisted of the prostate gland with a 5 mm periprostatic margins and the proximal 1.0 cm of the seminal vesicles with a resultant planning target volume of approximately 1.9 times the actual prostate volume [ 13 , 14 , 15 ]. All post-implant dosimetric calculations were based on day 0 evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Pre-planning technique, intraoperative approach, and dosimetric evaluation have previously been described in detail [ 13 , 14 ]. The brachytherapy target volume consisted of the prostate gland with a 5 mm periprostatic margins and the proximal 1.0 cm of the seminal vesicles with a resultant planning target volume of approximately 1.9 times the actual prostate volume [ 13 , 14 , 15 ]. All post-implant dosimetric calculations were based on day 0 evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Although a D 90 > 130 Gy is considered adequate by the American Brachytherapy Society [8], various studies have shown that a D 90 ≥ 140 Gy is associated with improved biochemical control [9, 10]. Previous studies have found that specific factors such as prostate volume, post-implant prostatic edema, and the number of seeds implanted can influence D 90 [11, 12, 13]. …”
Section: Purposementioning
confidence: 99%